The Impact of Information on the Willingness-to-Pay for Labeled Organic Food Products - Sandra Rousseau; Liesbet Vranken (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
Organic labels potentially play an important role in shaping consumer preferences for organic food products. Infirmation implied by the presence of labels can be used by consumers to facilitate their consumption decisions. Therefore, we investigate the influence of the provision of objective infirmation on the willingness-to-pay of consumers for labeled organic apples in Flanders (Belgium). Initially, we find that Flemish consumers are willing to pay a positive price premium of approximately 33 eurocent per kilogram for labeled organic apples. After the provision of infirmation on the actual environmental and health effects of organic apple production, this price premium becomes even more pronounced and amounts to approximately 56 eurocent per kilogram.
Keywords: Q01; Q51; D12; 330; organic food production; willingness-to-pay; choice experiment; role of information